Estudo de Efeitos Ambientais que Influem na Forma da Curva de Lactação de Cabras Mestiças no Estado da Paraíba - Ribeiro, Maria Norma [UNESP]; Pimenta Filho, Edgard Cavalcanti (My University, 1999)
The objective of this experiment was to study the effect of environmental factors on the shape of lactation curves (peak yield, time of peak and persistency) of crossbred Alpine x Gurguéia goats fitted by Incomplete gamma function. Data from 6126 records of 877 lactation of 366 goats raised on Carnaúba Farm, Taperoá city, Parafba State in the period from 1988 to 1995 were used. The function was fitted by linear regression, after logarithmic transformation and by non-linear iterative method. Adjusted coefficient of determination (R2a) for linear regression was 71% versus a R2a of 90% obtained by non-linear regression. Peak yield, time of peak and persistency were obtained by fitting the non-linear regression, that showed superior fit. The study of environmental effects on those traits was made by least squares method, including in the model the following factors: calving type, calving order, calving year and calving season. The environmental effects affected all the studied traits. Higher milk peak yields were observed for adult goats, which was justified by the complete physiological development of these animals.
Study of the Environmental Effects that Affect the Shape of Lactation Curves of Crossbred Goats in Paraíba State
Keywords: Goats; Incomplete gamma function; Lactation curve